INOVATION OF MILKS PRODUCT TO CRACKERS WITH TECHNOLOGY TRANSFER CABINET DRYER - Khothibul Umam Al Awwaly (Journal of Innovation and Applied Technology, 2017)
SMEs "RR Milk," a pioneer of SMEs that produce milk into milk crackers and milk candy in the Batu City. The production system on SMEs of dairy cows is still manual and if using household appliances scale still impacting on productivity that has not been maximized to meet market demand. The critical point of SME issues "RR Milk" was lack of technological innovation in the production system due to the use of manual production equipment mainly in the drying process of milk crackers. Through the help of technology transfer to procurement of machinery and equipment production guidance on the management of which the current management of the business is still conventional, less organized in a professional manner and therefore contributes to the progress of its business performance. The results showed that the implementation of activities coordination activities, mentoring and socialization of the means of production of milk crackers were good, production and financial recording system was good, and machinery equipment production facility in the form of the dryer cabinet has been done in order to improve the capacity and efficiency of the production of milk crackers. Mentoring activities packaging system (labeling) and marketing is also done with the target to expand market share and marketing systems more planned and strategic.